Use of Electronic Databases in University Libraries of British Columbia: a Study - Kaur, Amritpal; Randhawa, Sarwan Singh (Journal of Information and Knowledge, 2010)
The present study aims at analyzing the use of electronic databases in three universities of British Columbia. A well structured questionnaire was designed to collect the responses of the teachers and the students. The data was collected through a web based survey. One thousand teachers and students were requested to fill up the survey out of which 515 responses were received. The response rate was 51.5%. The study deals with the various aspects of the use of databases such as familiarity with databases, method of learning database use skills, frequency of database use, purposes for which the databases are used, success rate in finding the information, problems in finding the information, features of a good database and the most preferred databases. The results of the survey provide useful information about the use of databases. Some suggestions are put forth to make the databases more beneficial for studies and research purposes.